Developing Competencies for Technology- Pedagogy Integration among In-service Teachers: Reflections - Rathnabai S, Angel (Indian Journal of Educational Technology, 2024)
National Education Policy, 2020 (NEP-2020) of India emphasises the interplay of education and technology. The policy notes that one of the central principles to steer the education system will be the ‘extensive use of technology in teaching and learning, removing language barriers, increasing access as well as education planning and management’. In this context, ICT intervention in the school system to leverage the outcome of education is also a goal. To achieve this goal, human resources, i.e. teachers, are the game changers, and hence the emphasis lies on the capacity building of teachers. NEP 2020 recommends rigorous training in learner-centred pedagogy, teachers becoming high-quality eContent creators, and also integrating technology in the teaching-learning process. It also emphasises the teacher’s role in facilitating active student engagement with the content and with each other through the use of technology. Training teachers in the use of technology was emphasised through the ICT@School Scheme under RMSA, and also funds were provided for establishing infrastructure for technology in schools. The fourteen studies done as a third-party evaluation of the ICT@ School Scheme reveal that there is no systematic way for holistic training of teachers in the use of technology. Most of the training has focused only on office packages which couldn’t transform the teaching-learning process. Even when the Samagra Shiksha was launched, the ICT component in the Samagra shiksha clearly elaborates on the need for training teachers on the use of ICT and recommends systematic training. The budget announcement emphasises developing every teacher as a digital teacher. In this context, developing the competencies of teachers to integrate digital technology becomes the core goal of achieving quality education. Curricula for ICT in Education for School System developed by the Central Institute of Educational Technology (CIET), a constituent unit of the National Council of Educational Research and Training (NCERT) is a national curriculum to define the focus, content, and strategy for in-service training to build the competencies of teachers in integrating ICT in Education. This curriculum is being implemented to build the competencies of teachers in integrating content, pedagogy, and ICT in teaching and learning. It proposes a blended approach for training integrating face-to-face and online modes. This article brings out the features and scope of ICT in the education curriculum for teachers through the lessons learned for its implementation at various levels. Reflections based on the implementation bring out the need for systematic planning in training teachers, the content that can support the development of their knowledge and also the strategies to be followed for effective implementation. With this competency-based curriculum, it is possible to prepare teachers to face the expectations of the current digital era.